2021
DOI: 10.1002/aenm.202100158
|View full text |Cite
|
Sign up to set email alerts
|

Screening Nanographene‐Mediated Inter(Porphyrin) Communication to Optimize Inter(Porphyrin–Fullerene) Forces

Abstract: Multifunctional molecular materials comprising porphyrins and fullerenes have served as perfect prototypes to study key aspects of natural photosynthesis starting at light harvesting and energy transfer processes all the way to charge separation, charge shift, and charge recombination. Herein, hexa‐peri‐hexabenzocoronenes (HBCs) are explored, decorated with one, two, and six porphyrins at their peripheral positions, within the context of replicating key steps of photosynthesis. The major focus of the investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…368,369 p-Extended nanographenes with suitably sized cavities have also been utilized as hosts for fullerenes. [370][371][372] For example, Wang and coworkers reported a Janusarene 61, 342 possessing nineteen phenyl rings (seven constituting the hexaphenylbenzene core and the other twelve forming a ''fence'' around the two faces of the core), which was synthesized via an efficient cobalt-catalyzed cyclotrimerization of alkyne precursors. Hostguest complexation of 61 and C 60 was supported by SCXRD, which revealed a ratio of 1 : 1 in the solid state.…”
Section: Other Fullerene Hostsmentioning
confidence: 99%
“…368,369 p-Extended nanographenes with suitably sized cavities have also been utilized as hosts for fullerenes. [370][371][372] For example, Wang and coworkers reported a Janusarene 61, 342 possessing nineteen phenyl rings (seven constituting the hexaphenylbenzene core and the other twelve forming a ''fence'' around the two faces of the core), which was synthesized via an efficient cobalt-catalyzed cyclotrimerization of alkyne precursors. Hostguest complexation of 61 and C 60 was supported by SCXRD, which revealed a ratio of 1 : 1 in the solid state.…”
Section: Other Fullerene Hostsmentioning
confidence: 99%
“…Upon excitation and ISC, vibrationally hot 3 MLCT­(L p ) relaxed to the thermally equilibrated 3 MLCT­(L p ) in less than 10 ps, typical for VR processes in [Ru­(bpy) 3 ] 2+ and other ruthenium polypyridine chromophores. , Electronic coupling between the different excited states was strong, and it favored an efficient IC without any significant kinetic barriers (Figure , top), leading to the population of the lowest triplet state in a few picoseconds, like in [Ru­(bpy) 3 ] 2+ . Observations involving a variety of intramolecular donor/bridge/acceptor processes, ranging from singlet fission to ground- and excited-state intervalence charge transfers, , revealed that para connectivity promotes stronger electronic coupling than meta connectivity, suggesting that the topology of the bridge can be exploited to modulate excited-state electronic coupling. , Therefore, we hypothesized that the meta topology of the bridge in D m could lead to poor electronic coupling and thus to an anti-Kasha scenario, fulfilling the requirements for an anti-dissipative photosensitizer/photocatalyst. Thus, we sought to explore the IC/VR dissipative pathways of D m , by means of TAS in the femtosecond (fsTAS) and nanosecond (nsTAS) ranges.…”
Section: Introductionmentioning
confidence: 99%
“…19,32−38 In, e.g., multiporphyrinic HBC conjugates, the interporphyrinic communication was found to be mediated by the HBC backbone and the resulting geometry. 38 In the current systems, the peripheral positions of the HBCs are utilized to study the electron transfer interactions between (metallo)porphyrins and fullerenes one step ahead. We decorated the HBC platform with ZnP and C 60 to obtain geometrical isomers with electron donors and acceptors positioned in ortho-, meta-, and para-positions to each other (Figure 1A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hexa- peri -hexabenzocoronenes (HBCs) have recently attracted increasing attention due to their unique optoelectronic properties and the possibilities to utilize/tune or functionalize them. Multiple publications document the properties of HBCs regarding photon and charge management, as well as electronic communication. Noteworthy is the efficient coupling between HBCs and porphyrins. , In, e.g., multiporphyrinic HBC conjugates, the interporphyrinic communication was found to be mediated by the HBC backbone and the resulting geometry …”
Section: Introductionmentioning
confidence: 99%